2001
DOI: 10.1093/emboj/20.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Type III TGF-beta receptor-independent signalling of TGF-beta2 via TbetaRII-B, an alternatively spliced TGF-beta type II receptor

Abstract: Transforming growth factor-b (TGF-b) signals through membrane-bound serine/threonine kinase receptors, which upon stimulation phosphorylate Smad proteins and thereby trigger their nuclear translocation and transcriptional activity. Although the three mammalian isoforms of TGF-b are highly homologous at the level of sequence, analysis of their in vivo function by gene knockouts revealed striking differences, suggesting no signi®cant functional redundancy between TGF-b1, -2 and -3. While signal transduction by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1
5

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 63 publications
5
68
1
5
Order By: Relevance
“…4A). The dose-response curve obtained with increasing amounts of TGF-␤2 suggested that the cells are able to signal through TGF-␤2 in the absence of T␤RIII and T␤RII-B, but require higher doses of TGF-␤2 compared with TGF-␤1 or -␤3 (data not shown), as has been previously shown (16).…”
Section: Both Full-length T␤rii-b and T␤rii Expressed In L6 Cells Thasupporting
confidence: 75%
See 3 more Smart Citations
“…4A). The dose-response curve obtained with increasing amounts of TGF-␤2 suggested that the cells are able to signal through TGF-␤2 in the absence of T␤RIII and T␤RII-B, but require higher doses of TGF-␤2 compared with TGF-␤1 or -␤3 (data not shown), as has been previously shown (16).…”
Section: Both Full-length T␤rii-b and T␤rii Expressed In L6 Cells Thasupporting
confidence: 75%
“…It has been suggested that iodinated TGF-␤2 could be cross-linked to T␤RII-B but not T␤RII, thus indicating that the 26-amino acid insert might confer the ability to bind and signal via TGF-␤2 to the type II-B receptor (16). Indeed, the 26-amino acid insert is at the N 1 and 2) or presence of 5 g/ml each of sT␤RII-B.Fc, sT␤RII.Fc, or sT␤RI.Fc alone (lanes 3-5), or of the mixture composed of 5 g/ml each of sT␤RII-B.Fc or sT␤RII.Fc plus sT␤RI.Fc (lanes 6 and 7) as indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Interestingly, the expression of TbR-IIB is restricted to cells originating from mesenchymal tissues such as bone where the isoform TGF-b2 has a predominant role. It would be interesting to investigate an antisense OGN designed against this spliced variant, as it may be more specific in inhibiting TGF-b2-mediated activity.…”
Section: ----------------------------------------------------mentioning
confidence: 99%